F155. Age related characteristics and normative values of F wave in 229 healthy chinese infants. (May 2018) - Pan, Hua; Lin, Jinxi; Chen, Na; Jian, Fan; Zhang, Lei; Yang, Shuo; Wang, Ying; Wang, Yongjun; Guan, Yuzhou; Cui, Liying; Kimura, Jun
Abstract : Introduction: Clinical assessments of a peripheral neuropathy is difficult in infants. The conventional nerve conduction study also faces technical challenge in measuring the distances between the stimulating and recording electrodes. One cm error in surface measurement for such short limbs can change the conduction velocity by as much as 15%. The use of F-wave latencies, requiring no determination of limb length, may circumvent this problem, should we have a standardized nomogram for infants. This study describes age related characteristic and normative values of F-wave in healthy Chinese infants. Methods: We studied median, ulnar and tibial nerves on one side in 229 healthy Chinese infants (108 males) ranging from 1 to 12 months in age and 53–80 cm in height. All subjects had normal neurological examination, developmental assessment, family history and maternal gestational health. The infants, kept warm at 34 °C body temperature, lay supine in the mothers' arm, during electrophysiological examination that consisted of stimulating each nerve at the wrist or ankle 10 times and recording compound muscle action potentials (CMAP) and F waves. The measurement included CMAP amplitude and latency in addition to F-wave amplitude, persistence and minimal, maximal and mean latencies. Results: Contrary to our anticipated concerns dealing with small babies, all infants tolerated the procedure well, showing a high F-wave persistence [Median (P25-P75)] for median [100 (93–100)], ulnar [100 (92–100)] and tibial nerves [100 (100–100)]. In fact, 4 boys and 2 girls drifted into a light sleep during the procedure with a concomitant precipitous decline in persistence associated with a slight increase in latency. Considering only the data obtained while awake, minimal F-wave latencies showed a strong negative correlation to the age for median ( r  = −0.21, P  < 0.01), ulnar ( r  = −0.22, P  < 0.001) and tibial nerves ( r  = −0.30, P  < 0.001) and a positive correlation to the height only for the tibial nerve ( r  = 0.15, P < 0.05) and not for the median ( r  = −0.08, P > 0.05) or ulnar nerve ( r  = −0.02, P  > 0.05). The normal monthly range of minimal F-wave latencies (mean ± SD) for the tibial nerve, which probably serves best for clinical evaluation, comprised 23.26 ± 1.71, 20.89 ± 1.91, 21.36 ± 1.84, 20.28 ± 2.05, 20.41 ± 1.89, 21.21 ± 1.77, 20.43 ± 1.69, 21.42 ± 2.81, 20.77 ± 1.24, 20.40 ± 1.24, 20.72 ± 1.24 and 20.32 ± 1.35 ms for age 1–12 months. The F waves for the median and ulnar nerves, though shorter in latency, showed a similar pattern. Conclusion: We can elicit F waves easily in a study of infants as a reliable measure of nerve conduction, which shows a stronger correlation with age than with height, indicating rapid maturational changes during the first year of life. The normal latency ranges established in this study will serve as the basis for using F waves to assess infants with neuropathic disorders in lieu of the conventional nerve conduction study, which poses a major technical limitation for short limbs.